A Short History of the Genome-Wide Association Study: Where We Were and Where We Are Going - Shiro Ikegawa (Genomics & Informatics)
Recent rapid advances in genetic research are ushering us into the genome sequence era, where an individual's genome information is utilized for clinical practice. The most spectacular results of the human genome study have been provided by genome-wide association studies (GWASs). This is a review of the history of GWASs as related to my work. Further efforts are necessary to make full use of its potential power to medicine.